HISTORY OF ARABIC CURRICULUM DEVELOPMENT IN INDONESIA - faizin, khoirul; ismail, ismail (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
first curriculum was compiled until the latest curriculum in 2020, known as the